2004
DOI: 10.2105/ajph.94.2.205
|View full text |Cite
|
Sign up to set email alerts
|

Preventing 3 Million Premature Deaths and Helping 5 Million Smokers Quit: A National Action Plan for Tobacco Cessation

Abstract: In August 2002, the Subcommittee on Cessation of the Interagency Committee on Smoking and Health (ICSH) was charged with developing recommendations to substantially increase rates of tobacco cessation in the United States. The subcommittee's report, A National Action Plan for Tobacco Cessation, outlines 10 recommendations for reducing premature morbidity and mortality by helping millions of Americans stop using tobacco. The plan includes both evidence-based, population-wide strategies designed to promote cessa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
161
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(166 citation statements)
references
References 32 publications
4
161
0
1
Order By: Relevance
“…The latter is consistent with calls for training medical students and residents in tobacco prevention and control (Fiore, et al, 2004). A survey of pediatric residency training directors showed that most training programs do not include tobacco in their curriculum (Hymowitz, et al, 2001a), and training directors share the same concerns about addressing tobacco as their colleagues.…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…The latter is consistent with calls for training medical students and residents in tobacco prevention and control (Fiore, et al, 2004). A survey of pediatric residency training directors showed that most training programs do not include tobacco in their curriculum (Hymowitz, et al, 2001a), and training directors share the same concerns about addressing tobacco as their colleagues.…”
Section: Introductionsupporting
confidence: 57%
“…Collins, et al, 2007). Missed opportunities to intervene on tobacco in pediatric settings represent a gap in our nation's antismoking armamentarium (Fiore, et al, 2004). …”
Section: Introductionmentioning
confidence: 99%
“…The National Action Plan for Tobacco Cessation recommended that competency in tobacco dependence interventions be a core graduation requirement for all new physicians. 18,21 As medical schools increasingly incorporate smoking cessation counseling curricula and assessments, it is important to have evidence to demonstrate that counseling skills are retained. It has previously been demonstrated that first-year medical students can effectively learn smoking cessation counseling skills through enhanced curricula, 22,23 but retention has been less well studied.…”
Section: Discussionmentioning
confidence: 99%
“…Smoking is the most important preventable cause of premature death in the USA [1][2][3][4][5]. The Center for Disease Control (CDC) estimates that the medical costs of treating smokers is more than US$96 billion a year including another US$97 billion a year from lost productivity [6].…”
Section: Introductionmentioning
confidence: 99%
“…To impact national cessation rates, smoking cessation support must be widely disseminated and readily available [8]. Easily accessible public health interventions, like quitlines and quit smoking Internet systems, may improve smoking cessation rates [3,[9][10][11][12][13][14][15], but are under-utilized [16]. New methods are needed to proactively recruit smokers to these available, effective smoking cessation systems.…”
Section: Introductionmentioning
confidence: 99%